The Fraud Hexagon Model to Detect Financial Reporting Fraud in Mining Companies Listed on the Indonesia Stock Exchange - Retnowati, Wulan; Wahida, Nurul Aini; Satibi, M (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Research Background: The mining sector ranks third among the industries most affected by fraud, accounting for 5.0% of reported cases, following the financial and banking sector and government institutions. Instances of fraudulent financial reporting have also occurred within Indonesia’s mining sector. Introduction/Main Objectives: This study aims to examine whether financial targets, board changes, political ties, weak monitoring mechanisms, auditor turnover, and CEO duality affect financial statement fraud. Methods: The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. A total of 42 firms were selected through purposive sampling. Multiple linear regression analysis was employed using SPSS 25. Results: The findings show that financial targets and CEO duality positively influence financial statement fraud, while changes in directors have a negative effect. Meanwhile, political connections, ineffective monitoring, and auditor changes do not exhibit a significant impact on fraudulent financial reporting. Conclusion: Companies should enhance their corporate governance frameworks, particularly by limiting excessive CEO power and ensuring that leadership roles remain structurally independent. Organizations should also encourage leadership rotation to reduce opportunities for long-term manipulation.